2022
DOI: 10.5603/fm.a2021.0013
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric profile in foetuses and evolution of Achilles tendon

Abstract: Background: The Achilles tendon (AT) develops from the merge of the tendinous part of the gastrocnemius (GM) and soleus (SM) muscles. The AT is the structural base for the biomechanical work of the ankle joint. Understanding morphometry of the AT is crucial due to the tendon vulnerability to rupture and damage which requires further surgical repair and management. Despite its clinical significance, data concerns measurements of the AT in human fetuses are scare. The aim of our study was to assess the AT, GM an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…24 Interestingly, morphometric evaluaion of AT was also found to be conducted in human aborted fetuses in Poland where they found that there were no significant correlation between sex or side and size of AT in human fetuses. 27 In the present study the width at its origin was found to be more than the width at its insertion (Table 2 and Table 4) which was found to be decreasing from its origin to insertion site unlikely to that of the findings explained by other researcher 14 and this variation is explainable as the studies covered different population group.…”
Section: Discussioncontrasting
confidence: 42%
“…24 Interestingly, morphometric evaluaion of AT was also found to be conducted in human aborted fetuses in Poland where they found that there were no significant correlation between sex or side and size of AT in human fetuses. 27 In the present study the width at its origin was found to be more than the width at its insertion (Table 2 and Table 4) which was found to be decreasing from its origin to insertion site unlikely to that of the findings explained by other researcher 14 and this variation is explainable as the studies covered different population group.…”
Section: Discussioncontrasting
confidence: 42%
“…In adults, the average size of the AT is 15 cm (range, 11–26 cm), and the mean width is 6.8 cm at its origin, 1.8 cm at the midsection, and 3.4 cm at its insertion to the midpoint of the posterior surface of the calcaneus ( Doral et al, 2010 ). Furthermore, the proportion of gastrocnemius and soleus tendons involved in the composition of the AT slightly varies in different individuals ( Wasniewska et al, 2022 ). At approximately 8–10 cm above the termination, the gastrocnemius and soleus tendons fuse completely ( Ahmed et al, 1998 ).…”
Section: Anatomical Characteristics Of the Atmentioning
confidence: 99%